Comparative Genomics and Transcriptional Analysis of Flavobacterium columnare Strain ATCC 49512 - Tekedar, Hasan C.; Karsi, Attila; Reddy, Joseph S.; Nho, Seong W.; Kalindamar, Safak; Lawrence, Mark L. (Frontiers in Microbiology, 2017)
Flavobacterium columnare is a Gram-negative fish pathogen causing columnaris disease in wild and cultured fish species. Although the pathogen is widespread in aquatic environments and fish worldwide, little is known about biology of F. columnare and mechanisms of columnaris disease pathogenesis. Previously we presented the complete genome sequence of F. columnare strain ATCC 49512. Here we present a comparison of the strain ATCC 49512 genome to four other Flavobacterium genomes. In this analysis, we identified predicted proteins whose functions indicate F. columnare is capable of denitrification, which would enable anaerobic growth in aquatic pond sediments. Anaerobic growth of F. columnare ATCC 49512 with nitrate supplementation was detected experimentally. F. columnare ATCC 49512 had a relatively high number of insertion sequences and genomic islands compared to the other Flavobacterium species, suggesting a larger degree of horizontal gene exchange and genome plasticity. A type VI subtype III secretion system was encoded in F. columnare along with F. johnsoniae and F. branchiophilum. RNA sequencing proved to be a valuable technique to improve annotation quality; 41 novel protein coding regions were identified, 16 of which had a non-traditional start site (TTG, GTG, and CTT). Candidate small noncoding RNAs were also identified. Our results improve our understanding of F. columnare ATCC 49512 biology, and our results support the use of RNA sequencing to improve annotation of bacterial genomes, particularly for type strains.